Pengaruh Kombinasi ZPT IAA dan BAP terhadap Pertumbuhan Eksplan Vanili (Vanilla planifolia Andrews) secara In Vitro - Duri, Rijal Daivu (Agropross : National Conference Proceedings of Agriculture, 2022)
Vanilla (Vanilla planifolia Andrews) is one of the commodity values of plantation crops in Indonesia which has a high economy. Vanilla cultivation is done to get vanilla fruit which is the raw material for making vanilla essence. Vanilla can be cultivated generatively and vegetatively. However, in the field, generative cultivation of vanilla through seeds is considered very detrimental. Because it takes a long time and a low success rate. Meanwhile, vegetative cultivation of vanilla through cuttings is also considered less effective. Because, often seedlings from tendril cuttings are susceptible to stem rot disease and their growth is not uneven. So that planting on a large scale will be difficult to do. Therefore, to obtain more vanilla seeds, it is necessary to use certain technologies such as in vitro. The purpose of this research was to determine the effect of the combination ZPT IAA and BAP on the growth of vanilla explants. The research used was RAL non-factorial with 5 treatments, namely P1 (0 ppm IAA + 2 ppm BAP), P2 (0,1 ppm IAA + 1,5 ppm BAP), P3 (0,3 ppm IAA + 1 ppm BAP), P4 (0,5 ppm IAA + 0,5 ppm BAP), and P5 (0,7 ppm IAA + 0 ppm BAP). Each treatment was repeated 5 times. The basic media used is MS. The results showed that the P3 and P5 treatments affected the ability to explants germinate, explants did not stagnate, and explants form shoots. However, all treatments did not affect the ability of explants to produce roots.